Evaluation of the Acoustic Performance of Porous Materials Lined Ducts with Geometric Discontinuities - TOUNSI, Dhouha; TAKTAK, Wafa; DHIEF, Raja; TAKTAK, Mohamed; CHAABANE, Mabrouk; HADDAR, Mohamed (Archives of Acoustics, 2022)
Duct silencers provide effective noise reduction for heating, ventilation and air conditioning systems. These silencers can achieve an excellent sound attenuation through the attributes of their design. The reactive silencer works on the principle of high reflection of sound waves at low frequencies. On the other hand, the dissipative silencer works on the principle of sound absorption, which is very effective at high-frequencies. Combining these two kinds of silencers allowed covering the whole frequency range. In this paper, the effect of liner characteristics composed of a perforated plate backed by a porous material and geometry discontinuities on the acoustic power attenuation of lined ducts is evaluated. This objective is achieved by using a numerical model to compute the multimodal scattering matrix, thus allowing deducing the acoustic power attenuation. The numerical results are obtained for six configurations, including cases of narrowing and widening of a radius duct with sudden or progressive discontinuities. Numerical acoustic power attenuation shows the relative influence of the variation in the values of each parameter of the liner, and of each type of radius discontinuities of ducts.